KEY CONDITIONS OF DEVELOPMENT OF PSYCHOLOGICAL-PEDAGOGICAL COMPETENCE OF TEACHERS OF SPECIAL DISCIPLINES OF TECHNICAL COLLEGE - С. Садовенко (Київський національний університет імені Тараса Шевченка, 2020)
The article analyzes conditions of development of psychological and pedagogical competence of teachers of special disciplines of technical colleges as a determining factor in the preparation of a highly qualified graduate.An author's scheme of scientific and methodological work of a technical college is proposed, which combines components, principles and functions of the system and conditions of its effective functioning, in which all structural components of the system (goals and objectives, content, forms and methods) are aimed at realizing the result of work and associated with the conditions, principles and functions, and the integrity and systematic use of all the components identified in the complex will contribute to the end result.It is emphasized that an important factor for becoming a beginning teacher is the moral and financial support of a pedagogical employee by the administration of an educational institution. The priority goal of improving the teachers training system is the principle of accessibility of methodological-educational services and orientation to the individual needs of each teacher, and among the ways of solving the set tasks - full-scale introduction of modern computer technologies of teaching.The key conditions for the development of psychological and pedagogical competence of teachers of special disciplines of technical colleges have been formulated, namely: the creation of a system of scientific and methodological work in the educational establishment, which allows to develop the psychological and pedagogical competence of teachers of special disciplines of technical colleges, the formation of internal and external disciplines of teaching professional activity in a technical college, providing scientific and methodological system of educational establishment with information, in particular clouds technology.It is concluded that the implementation of the above-mentioned organizational and pedagogical conditions into the scientific and methodological process of the technical college will become the foundation for the further formation and development of the psychological and pedagogical competence of teachers of special disciplines.

Проаналізовано проблему розвитку психолого-педагогічної компетентності викладачів спеціальних дисциплін технічних коледжів як визначальний фактор підготовки висококваліфікованого випускника, визначені протиріччя, що існують у системі сучасної методичної роботи. Запропоновано авторську схему науково-методичної роботи технічного коледжу, яка об'єднує компоненти, принципи та функції системи й умови її ефективного функціонування. Сформульовано ключові умови розвитку психолого-педагогічної компетентності викладачів спеціальних дисциплін технічних коледжів: створення в закладі освіти системи науково-методичної роботи, формування внутрішньої та створення зовнішньої мотивації викладачів спеціальних дисциплін до професійної діяльності в технічному коледжі, забезпечення науково-методичної системи закладу освіти інформаційними, технологіями. Зроблено висновок, що втілення в науково-методичний процес технічного коледжу вищезазначених організаційно-педагогічних умов стане фундаментом для подальшого формування й розвитку психолого-педагогічної компетентності викладачів спеціальних дисциплін.
КЛЮЧОВІ УМОВИ РОЗВИТКУ ПСИХОЛОГО-ПЕДАГОГІЧНОЇ КОМПЕТЕНТНОСТІ ВИКЛАДАЧА СПЕЦІАЛЬНИХ ДИСЦИПЛІН ТЕХНІЧНОГО КОЛЕДЖУ
Keywords: умови розвитку; психолого-педагогічна компетентність; технічний коледж; науково-методична робота.; developmental conditions; psychological and pedagogical competence; technical college; scientific and methodology.